The Age of the Warrior : Selected Writings - Fisk, Robert (London Fourth Estate, 2008)
A selection of Robert Fisk's finest 'Comment' pieces from the Saturday Independent. He is best known for his writing about the Middle East, its wars, dictators and international relations, but these 'Comment' articles cover an array of topics, from his soldier grandfather to handwriting to the Titanic.
Include Index.
A selection of Robert Fisk's finest 'Comment' pieces from the Saturday 'Independent'.
Keywords: War and society -- Mass media--Social aspects -- Foreign correspondents -- War correspondents -- World politics -- Fisk, Robert